The impact of job rotation towards motivation of nurses in Private Medical Institution in Malaysia / Norlida Zakirai@Zakaria ... [et al.] - Zakirai@Zakaria, Norlida; Eshak, Erratul Shela; Mohd Jidi, Munirah; Jamian, Nur Faithzah; Mohd Yusof, Aini Qamariah (UiTM Cawangan Johor, 2019)
Job rotation is one of the excellent tools in on job training. This study attempts to examine the impact of job rotation towards motivation of nurses in private medical institutions. Among the three important outcomes of job rotation investigated further in this study are reducing stress, acquiring knowledge and skills as well as improving level of social interaction. Data was collected from 150 nurses in one established private medical institution in Melaka. Findings from this survey support three hypotheses: First, there is positive relationship between knowledge and skill acquired through job rotation that develops motivation of employees. Second, there is a positive relationship between increasing social interaction toward motivation of nurses. Third, there is no relationship between reducing stress towards motivation of nurses. This study is only limited to healthcare setting context. Further research should be conducted in different fields and examine different issues to investigate other impacts of job rotation on employees.